(untitled) (ModaPalavra e-periódico, 2013)
This essay aims to examine ways of teaching fashion with an emphasis on the creative process. This will be through the triangular approach of Barbosa (1998), methodology in which the author preconizes the axes reading, contextualization and production for the teaching of art. Thus, from the vertex of context, by reading of the teaching fashion, it will be observed the creative process of the fashion, viewing how the aesthetic experience can contribute to this end. This aiming to interpret the relationship artistic context eaching fashionprocess, in order to base a study about the creative process, allocated at the apex of production, in addition to create teaching strategies that foment students’ authorship.